Ultrathin Ti3C2Tx (MXene) membrane for pressure-driven electrokinetic power generation - Yang, Guoliang; Lei, Weiwei; Chen, Cheng; Qin, Si; Zhang, Liangzhu; Su, Yuyu; Wang, Jiemin; Chen, Zhiqiang; Sun, Lu; Wang, Xungai; Liu, Dan (Nano energy, 2020)
Harvesting energy from natural or daily mechanical movements is an economic and environment-friendly way to alleviate energy shortage. Here we demonstrate a two-dimensional (2D) electrokinetic energy conversion device based on ultrathin laminated Ti3C2Tx membrane (TCM) driven by pressure gradients. The applied pressure, pH, lateral size of Ti3C2Tx nanosheets and membrane thickness were investigated. The results revealed that these parameters could remarkably regulate the electricity generation with TCMs. The TCMs with abundant negatively charged 2D nanocapillaries produced high streaming current density of 1.3 mA m−2 and output power density of 0.29 μW m−2 under 5 kPa in 0.01 M aqueous solution of sodium chloride. The MXene membrane generators present good solution compatibility for electrolytes in different alkali metal ions and wide pH range (4–10). This work extends the application of MXenes providing a new platform for energy conversion from natural and daily-life environment. Based on the principle of electrokinetic energy conversion, we reported a two-dimensional Ti3C2Tx (MXene) membrane device for harvesting energy from natural or daily mechanical movements. Streaming current is generated continuously under pressure gradients. The devices can be operated in various electrolytes and wide pH range. [Display omitted] •A pressure-driven electric generator based on stacked Ti3C2Tx nanosheets.•Electricity generation from mechanical forces.•Negatively charged surface and ultrathin structure for high streaming current.•Good solution compatibility in various electrolytes and wide pH range.